Second Five Year Plan Bombay State Buldana District - Government of Bombay (Government of Bombay, 1958)
The Second Five-Year Development Plan for Buldana District, initiated in 1958, presents a comprehensive strategy aimed at improving the district’s socio-economic conditions through targeted development in agriculture, irrigation, education, health, infrastructure, and social welfare. Covering an area of 3,760 square miles with a population of 870,168 residing in 1,188 villages, the district is predominantly agrarian, with nearly 80% of its population dependent on agriculture and major crops including jowar, cotton, and wheat. The plan focuses on strengthening agricultural productivity through the expansion of cultivation over 16 lakh acres, improved seed distribution via government seed farms, and enhanced crop protection measures. Irrigation development is a major priority, with proposals for minor irrigation tanks, wells, and the significant Nalganga River Project expected to irrigate approximately 22,000 acres primarily for cotton cultivation. The plan also emphasizes the development of animal husbandry through expanded veterinary services, breeding centers, and vaccination programs to control diseases such as rinderpest. Educational reforms include the expansion of primary schools, the introduction of free and compulsory education for children aged 6–14, the development of basic schools focusing on practical learning, and improvements in educational infrastructure. Health initiatives aim to strengthen rural healthcare by establishing new primary health centers and intensifying disease control programs, particularly for malaria, while improving maternal and child health services. Infrastructure development focuses on upgrading transportation networks through road construction and asphalting, as well as promoting rural electrification to support agricultural activities and local industries. The plan further encourages the formation of cooperative societies to strengthen rural credit systems and promote economic stability, alongside social welfare initiatives such as the Sarvodaya Scheme targeting the development of backward and tribal regions. Public awareness and community engagement are promoted through educational outreach programs, local media, and community centers. Additionally, the document includes several corrections and updates related to terminology, project timelines, road names, educational infrastructure data, and welfare program clarifications to ensure accurate representation of developmental activities. Overall, the plan outlines an integrated and participatory approach to rural development, aiming to raise living standards, strengthen economic productivity, and promote sustainable growth in Buldana District during the Second Five-Year Plan period.
Buldana District
Buldana District
Keywords: State Five Year Plan; Buldana District Development; Agricultural Development; Irrigation Expansion; Animal Husbandry Services; Educational Expansion; Rural Health Services; Infrastructure Development; Cooperative Societies; Rural Electrification; Community Development Programs; Social Welfare Initiatives